Cuproptosis key gene FDX1 is a prognostic biomarker and associated with immune infiltration in glioma - Lu, Hanwen; Zhou, Liwei; Zhang, Bingchang; Xie, Yuanyuan; Yang, Huiyin; Wang, Zhanxiang (Frontiers in Medicine, 2022)
Recent studies have found that the protein encoded by the Fdx1 gene is involved in mediating copper death as a regulator of protein lipoylation, and it is found to be related to the immune response process of tumors in some tumors. However, the specific biological function of FDX1 in glioma is currently unclear. To explore the potential function of FDX1 in glioma, this study explored the correlation between the expression of FDX1 in pan-cancer and glioma and survival prognosis by analyzing the public databases of GEPIA and Cbioportal. Tumor immune infiltration was analyzed by the TIMER2.0 database in tumors. The possible biological processes and biological functions of FDX1 in glioma were annotated through gene enrichment; the relationship between copper death represented by FDX1 and autophagy was explored through gene co-expression studies. Ultimately, the study draws the following conclusions: (1) FDX1 is highly expressed in gliomas and is associated with poor prognosis in low-grade gliomas (LGG); (2) Gene annotation indicates that FDX1 is mainly involved in the tumor protein lipoylation and cell death ; (3) FDX1 expression is positively correlated with the infiltration of some immune cells; (4) LIPT2 and NNAT, two other genes involved in lipoylation, may be unidentified marker gene for copper death. And the copper death genes related to Fdx1 were positively correlated with the expression of autophagy marker genes Atg5, Atg12 and Beclin-1. This evidence suggests that FDX1-mediated copper death may be an autophagy-dependent programmed death similar to ferroptosis, and that FDX1 may serve as a potential immunotherapy target and a prognostic marker for glioblastoma multiforme (GBM).